2013
DOI: 10.1155/2013/859056
|View full text |Cite
|
Sign up to set email alerts
|

Transient Limb Ischemia Alters Serum Protein Expression in Healthy Volunteers: Complement C3 and Vitronectin May Be Involved in Organ Protection Induced by Remote Ischemic Preconditioning

Abstract: The protective mechanism underlying remote ischemic preconditioning (RIPC) is unclear. This study aims to verify whether the protein expression profile in the serum could be altered by RIPC and to detect potential protein mediators. Transient limb ischemia consisting of three cycles of 5-min ischemia followed by 5-min reperfusion was performed on sixty healthy volunteers. Serum samples were collected at 30 min before transient limb ischemia and at 1 hour (h), 3 h, 8 h, 24 h, and 48 h after completion of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Surprisingly, only one of the given protein accession numbers could be found in both the mass spectrometry and the 2D gel result sets. Subsequently, Pang et al found 14 proteins to be differentially regulated by RIPC and validated these findings by Western blotting [18] . Notably, only one of the accessions reported, Gelsolin (UniProt accession number P06396), could be mapped to those published by Hepponstall et al Additionally, albeit with different sequences, both studies underlined the regulation of Apolipoprotein A-I.…”
Section: Introductionmentioning
confidence: 86%
“…Surprisingly, only one of the given protein accession numbers could be found in both the mass spectrometry and the 2D gel result sets. Subsequently, Pang et al found 14 proteins to be differentially regulated by RIPC and validated these findings by Western blotting [18] . Notably, only one of the accessions reported, Gelsolin (UniProt accession number P06396), could be mapped to those published by Hepponstall et al Additionally, albeit with different sequences, both studies underlined the regulation of Apolipoprotein A-I.…”
Section: Introductionmentioning
confidence: 86%
“…82,83 No consistent effect on secondary hemostasis has been found in healthy subjects and patients as well as in patients undergoing surgery. [21][22][23]26,54,78,79 The intervention increased fibrinolysis in patients with cerebrovascular disease and chronic ischemic heart failure, 25,26 but not in healthy males, 23,24 and the effects on fibrinolysis have not Liver resection (n ¼ 7): no effect on secondary hemostasis 10,[31][32][33][34]36,37 Cardiac procedures (n ¼ 2): reduced platelet activation 41,44 PCI (n ¼ 1): no effect on MI 40 Liver resection (n ¼ 9): no effect in eight studies 10,[30][31][32][33][34]36,37 Reduced intraop. bleeding in one study 35 Cardiac surgery (n ¼ 2): no effect 42,43 Remote ischemic conditioning Liver transplantation (n ¼ 1): no effect on secondary hemostasis 54 Aneurysmal subarachnoid hemorrhage (n ¼ 1): increased PT/INR but not PTT 78 Cardiac procedures (n ¼ 2): reduced platelet activation 82,83 Vascular surgery (n ¼ 8): no effect in seven studies [45][46][47][48]…”
Section: Discussionmentioning
confidence: 99%
“…89 Remote ischemic conditioning influenced laboratory parameters of hemostasis in study participants with no ischemic event close to the intervention. 21,22,25,26,78,79 Hence, the intervention could modulate hemostasis by directly affecting platelets or the fibrinolytic system without a preceding ischemic event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular interest was given to samples from sagittal sinus because they were taken behind the blood-brain barrier. Based on previous literature on protein functions and possible relevance to RIPC [19,21,30] we selected 4 proteins:, apolipoprotein E (APOE), complement C3 (C3), transthyretin (TTR) and vitronectin (VTN), to be validated by ELISA. The levels of these four proteins were, however, not significantly changed between the RIPC and control groups at any of the studied time points ( Figure 6).…”
Section: Proteomics Analysis Of Serum Samplesmentioning
confidence: 99%